2018
DOI: 10.1155/2018/6358485
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Pheochromocytoma, Paraganglioma, and Papillary Thyroid Carcinoma without Known Mutation

Abstract: Background Pheochromocytoma/paraganglioma is a rare tumor from neuroendocrine cells. 1/3rd of cases have germline mutations. Papillary thyroid carcinoma (PTC) is a common neoplasm from follicular cells of the thyroid. We report a case of pheochromocytoma/paraganglioma and PTC with negative testing for common mutations. Case 32-year-old male with incidental liver mass during laparoscopy for acute appendicitis. His symptoms included abdominal pain and profuse axillary hyperhidrosis. MRI showed an 11x12x14 cm cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…The survey period for the GAPP studies ranged from 2014 to 2018. Four studies reporting the GAPP scores for PCCs were originally identified [2,24,26,31], but only three met all our inclusion criteria and were included in this meta-analysis [2,24,26]. In total, out of 199 PCCs, GAPP scores were retrievable from 175 PCCs, of which four were malignant (2%) (Table 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The survey period for the GAPP studies ranged from 2014 to 2018. Four studies reporting the GAPP scores for PCCs were originally identified [2,24,26,31], but only three met all our inclusion criteria and were included in this meta-analysis [2,24,26]. In total, out of 199 PCCs, GAPP scores were retrievable from 175 PCCs, of which four were malignant (2%) (Table 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Gene mutations such as EGLN1, FH, KIF1B, MEN1, NF1, RET, SDHAF2, SDHC, SDHD, TMEM127, VHL and SDHA were all negative. In the case, it is not clear whether the occurrence of paraganglioma/pheochromocytoma/thyroid papillary carcinoma is accidental or caused by underlying genetic susceptibility [38].…”
Section: Clinical Manifestation and Monitoring Of Tmem127mentioning
confidence: 99%
“…También hasta un 45% pueden tener alguna mutación de fondo sin historia familiar por ser de penetrancia incompleta. Se han descrito varias mutaciones, siendo las más comunes las de Von Hippel-Lindau, del complejo succinato deshidrogenasa D, B y C, las del protooncogen RET y las de Neurofibromatosis tipo 1 (8)(9)(10)(11) . Un 10% de los pacientes tienen un síndrome hereditario relacionado al tumor, por ejemplo MEN IIA/IIB, Esclerosis Tuberal, Feocromocitoma Familiar, entre otras (6) .…”
Section: Bioquímicounclassified